The collection of 19th century printed Malay books of Emil Lüring - Warnk, Holger (Universiti Kebangsaan Malaysia, 2010)
Emil Lüring was a missionary of the Methodist Episcopal Church based in Singapore, Ipoh and Penang, from 1889 to 1909. After his return to Germany he became a lecturer at the Methodist Training Seminary in Frankfurt. During his stay in Malaya, he kept close connections on leading European experts on Malay languages and literature, such as Wilkinson, Shellabear, Blagden and Skeat. He was able to obtaine an impressive collection of early printed Malay books which he either received from the American Mission Press or bought himself from local publishing houses or booksellers in Singapore and Riau. Many of these titles are today extremely rare and are listed here